Investigation of thermal properties of Al1050/SS304 sandwich composite sheet by using a numerical, analytical and experimental approach - Atul S Takalkar; Lenin Babu Mailan Chinnapandi (Materials Research Express, 2020)
The utilization of the sandwich composite sheets for the specific industrial application depends upon its material properties. The present study investigates the mechanical and thermal properties of Al1050/SS304 sandwich composite sheets which could be used for the manufacturing of automobile sheet metal components such as a car body. The XRD (X-ray powder diffraction) and FTIR (Fourier-transform infrared spectroscopy) are performed to investigate the molecular structural arrangement and adhesive bonds whereas the composite wall test is performed to investigate the thermal conductivity by using different approaches. The experimental approach integrated with the analytical approach is utilized to validate the obtained thermal conductivity using a numerical approach. The thermal conductivity of 2.84 W mK ^−1 is obtained by using a numerical approach which is in good correlation with the experimental results.